THE IMPLEMENTATION OF PROJECT-BASED LEARNING IN TEACHING WRITING RECOUNT TEXT - Muhammad Farich; Haris Dibdyaningsih; Ahmad Syafi’I (Journal of English Language Teaching and Islamic Integration, 2023)
This study was carried out to describe the implementation and the quality of project based learning in teaching writing recount text to tenth grader. A qualitative descriptive research design was employed in this study. This study involved 15 students from tenth grader of one Islamic private school in Gresik. The data was obtained from observation and writing test. Students should make a book compilation in a class project. The findings showed that the implementation and the quality of project based learning achieve very good. The percentage of the implementation of project based learning reached 89%. So, the project based learning could be categorized as well implemented. Moreover, the percentage of students’ achievement which passed the standard reached 87%. So, the quality of the learning viewed from students’ writing achievement is considered as have a very good quality.